Navigating Climate Risk Through SFAS: A Sustainable Accounting Strategy - Aptasari, Fety Widianti; Falah, Muhammad Helmi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
limate change has become a pressing global issue with far-reaching impacts on various sectors, especially heavy industries such as manufacturing, mining, energy and metals. This phenomenon affects the operations and sustainability of these sectors through physical risks, such as natural disasters, and transition risks from climate change policies. This study aims to explore the application of Indonesian Financial Accounting Standards (SFAS) in the context of climate change impacts, focusing on SFAS 74 on insurance contracts, SFAS 71 on financial instruments, and SFAS 68 on fair value measurement. The results show that these three accounting standards complement each other in managing climate change risks. SFAS 74 improves the accuracy of measuring insurance liabilities related to natural disasters, while SFAS 71 addresses financial instrument risk by considering the impact of climate change on market value. SFAS 68 plays an important role in measuring the fair value of physical assets affected by environmental change. The integration of guidance from IFRS S2 and TCFD into SFAS is expected to improve transparency and consistency in climate change risk reporting, facilitate better risk management, and support more informed investment decisions. This research also identifies challenges in implementation and provides recommendations for adaptation of accounting standards to address climate change risks more effectively.